Democracy and socio-economic inclusion in Nigeria: reducing the mutual exclusivity through Islamic microfinance - Adewale, Abideen Adeyemi; Haron, Razali (IIUM Press, 2017)
Nigeria’s return to democratic rule about 18 years ago heralded a new beginning that was expected to promote political stability, ensure economic prosperity and build societal civility. However, Nigeria is now politically disintegrated, socially dislocated and economically unstable mainly due to many reasons but chiefly socio-economic exclusion. Notwithstanding its large Muslim population, policy recommendations from the West towards solving its myriad of political-economy issues often discounts Islamic alternatives. This has brought to the fore a challenge to the status quo as well as the philosophy that underlines Nigeria’s political-economy inclinations and implications for its teeming population. The objective of this theoretical paper is to stimulate discourse on the policy directions that are in alignment with political economy reality of Nigeria as a Muslim majority country. Specifically, this paper profiles Nigeria’s current socio-economic realities, and its political economy vis-à-vis the global economic order. The paper argues that the various Islamic social finance platforms especially Islamic microfinance may play a big role in mitigating the mutual exclusivity of democracy and socio-economic inclusion of Nigerians especially the Muslims.